(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The rapid pace of the scientific and technological revolution in the 1970s led to the possibility of using magnetic resonance imaging, based on the phenomenon of nuclear magnetic resonance, in medical diagnostics. The effect of nuclear magnetic resonance was discovered in the mid-1940s and for almost 30 years was used exclusively for scientific purposes in physics and chemistry [Keevil SF, 2001]. This method opened up excellent prospects for clinicians in the diagnosis of cardiovascular and endocrine diseases, neoplastic processes of various localizations, pathologies of the musculoskeletal system and neurological disorders of various etiologies [Kurbatov V.P., 2003; Wimmer V., 1990; Bloem JL, 2000; Soto J.A., 2000].